2021
DOI: 10.48550/arxiv.2110.06390
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Learning ground states of quantum Hamiltonians with graph networks

Abstract: Solving for the lowest energy eigenstate of the many-body Schrodinger equation is a cornerstone problem that hinders understanding of a variety of quantum phenomena. The difficulty arises from the exponential nature of the Hilbert space which casts the governing equations as an eigenvalue problem of exponentially large, structured matrices. Variational methods approach this problem by searching for the best approximation within a lower-dimensional variational manifold. In this work we use graph neural networks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Later on, convolutional neural networks (CNNs) [Liang et al 2018;Choo et al 2019;Szabó and Castelnovo 2020] are applied to 2D square lattices and are found to represent highly entangled systems effectively. However, CNN cannot be naturally used on non-grid lattices or even random graphs, which necessitated the exploration of graph neural networks (GNNs) [Yang et al 2020;Kochkov et al 2021a] for dealing with arbitrary geometric lattices. Moreover, autoregressive and recurrent neural networks (RNNs) are applied to represent quantum states, enabling direct sampling of spin configurations [Sharir et al 2020;Hibat-Allah et al 2020;].…”
Section: Existing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Later on, convolutional neural networks (CNNs) [Liang et al 2018;Choo et al 2019;Szabó and Castelnovo 2020] are applied to 2D square lattices and are found to represent highly entangled systems effectively. However, CNN cannot be naturally used on non-grid lattices or even random graphs, which necessitated the exploration of graph neural networks (GNNs) [Yang et al 2020;Kochkov et al 2021a] for dealing with arbitrary geometric lattices. Moreover, autoregressive and recurrent neural networks (RNNs) are applied to represent quantum states, enabling direct sampling of spin configurations [Sharir et al 2020;Hibat-Allah et al 2020;].…”
Section: Existing Methodsmentioning
confidence: 99%
“…They use the cosine function as the activation function for predicting the sign, which is suitable for capturing the oscillating features of the input spins. Kochkov et al [2021a] predicts log amplitude and phase of wave functions separately and shows that predicting phase directly enables effective generalization of the learned sign structure. Szabó and Castelnovo [2020] models amplitude and sign structure using two real-valued neural networks.…”
Section: Existing Methodsmentioning
confidence: 99%
“…In machine learning, structured objects such as molecules [14,50], proteins [9,16,33,37,28], materials [51], and quantum systems [31] are usually modeled as graphs. Original modeling shows basic connections between units and the resulted data type is known as 2D graphs.…”
Section: Introductionmentioning
confidence: 99%
“…The J 1 -J 2 model has also been investigated in Refs. [12][13][14][15][16] using the neural network ansatz. In a broader context, recent work has revealed a remarkable connection between the neural-network and the tensornetwork representation of quantum many-body states despite their differences in appearance and origin [17][18][19].…”
Section: Introductionmentioning
confidence: 99%